Improving Outpatientâs Quality of Life Through Patient Adherence of Antihypertensive Therapy Using âMobile Phone (SMS) and Brief Counselingâ5Aâ in Polyclinic of Internal Medicine at PKU Muhammadiyah Bantul Hospital, Yogyakarta - Saputri, Ginanjar Zukhruf; Akrom, Akrom; Darmawan, Endang (Indonesian Journal of Clinical Pharmacy, 2017)
Â The Health-Related Quality of Life (HRQoL) is one of the important psycho-social characteristics that can affect patientâs ability to manage therapy. Poor of knowledge of hypertension and the changing lifestyle can affect the quality of life of patients. One of the pharmacistâs interventions in hypertension management is to conduct counseling. Motivational counseling helps health service to assess patientâs understanding and patientâs readiness to change patientâs behavior. Some motivational counseling methods still need to be developed. Therefore, this study aims to find the influence of the